2011
DOI: 10.1016/j.vetpar.2010.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Development of an indirect ELISA-NcSRS2 for detection of Neospora caninum antibodies in cattle

Abstract: Neosporosis is of alarming economic concern in the cattle industry. The effectiveness of diagnostic tests for detecting specific antibodies against Neospora caninum is hampered by potential cross-reaction with other coccidia. Use of a single specific antigen might improve test specificity. An indirect enzyme-linked immunosorbent assay (ELISA) was developed using the truncated protein NcSRS2 expressed in Escherichia coli. The ELISA results were compared with those of the indirect fluorescence antibody test (IFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
0
17
0
1
Order By: Relevance
“…Further serological methods to diagnose N. caninum infection based on recombinant antigens are under development (Borsuk et al, 2011). Previous studies had indicated that the detection of pregnancy-associated substances could aid diagnosis of neosporosis abortion.…”
Section: Diagnosismentioning
confidence: 99%
“…Further serological methods to diagnose N. caninum infection based on recombinant antigens are under development (Borsuk et al, 2011). Previous studies had indicated that the detection of pregnancy-associated substances could aid diagnosis of neosporosis abortion.…”
Section: Diagnosismentioning
confidence: 99%
“…It is conserved in different isolates and is the immunodominant antigen recognized by serum from naturally infected animals (HOWE et al, 1998). In previous studies, recombinant NcSRS2 protein was used to develop ELISA tests for diagnosing of N. caninum infection and, in most of them, the protein was expressed through a prokaryotic system (GATURAGA et al, 2005;LIU et al, 2007;BORSUK et al, 2011;SA et al, 2014) or using a baculovirus approach (NISHIKAWA et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This protein has been expressed on different platforms, including baculovirus systems (NISHIKAWA et al, 2001(NISHIKAWA et al, , 2002 and Escherichia coli (BORSUK et al, 2011;GATURAGA et al, 2005;LIU et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The parasites could be detected not only macroscopically (the blue pellet was visible after centrifugation), but also microscopically (either isolated or after invasion in Vero cells). As this was an enzymatic reaction, the colour appeared as a complement for the detection and quantification by microscopic counting, which, for N. caninum, was mainly based on immunofluorescence [21,22], immunohistochemistry [23] and direct staining [9,24]. The detection of tachyzoites under different stages of replication in Vero cells opens up the possibility of refining the assay via the substitution of 5 coding sequence flanking regions, which can improve or decrease the X-Gal precipitation or have a time-specific expression for detection in different periods of the life cycle, as seen for the promoter of BAG1 activated in the bradyzoite stage [25].…”
Section: Discussionmentioning
confidence: 99%